2019
DOI: 10.1096/fj.201802351r
|View full text |Cite
|
Sign up to set email alerts
|

M1 muscarinic receptors regulate the phosphorylation of AMPA receptor subunit GluA1 via a signaling pathway linking cAMP‐PKA and PI3K‐Akt

Abstract: Ml muscarinic acetylcholine receptors are highly expressed in key areas that control cognition, such as the cortex and hippocampus, representing one potential therapeutic target for cognitive dysfunctions of Alzheimer's disease and schizophrenia. We have reported that M1 receptors facilitate cognition by promoting membrane insertion of α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid receptor AMPA receptor subunit 1 (GluA1) through phosphorylation at Ser845. However, the signaling pathway is still unclear.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…Likewise, the WNT/β‐Catenin pathway also influences the transcription and activity of Tcf4 because the activation of WNT/β‐Catenin mediated by pharmacological intervention increased TCF4 mRNA levels (Hennig et al, 2017). Some evidence involving changes in WNT/β‐Catenin pathway and schizophrenia includes shortening of cell cycle (Fan et al, 2012), weakening of the blood‐brain‐barrier associated with alterations in PKA (Nishiura et al, 2017), and disruptions in glutamatergic signaling (Uematsu et al, 2015; Zhao et al, 2019). Complementary evidence of disruption in the WNT pathway includes hyperactivation in the presence of DISC‐1 (Brandon et al, 2009), imbalance between canonical and non‐canonical signaling, and altered mRNA levels of WNT‐related genes (Hoseth et al, 2018).…”
Section: Ndd‐associated Multifactorial Disordersmentioning
confidence: 99%
“…Likewise, the WNT/β‐Catenin pathway also influences the transcription and activity of Tcf4 because the activation of WNT/β‐Catenin mediated by pharmacological intervention increased TCF4 mRNA levels (Hennig et al, 2017). Some evidence involving changes in WNT/β‐Catenin pathway and schizophrenia includes shortening of cell cycle (Fan et al, 2012), weakening of the blood‐brain‐barrier associated with alterations in PKA (Nishiura et al, 2017), and disruptions in glutamatergic signaling (Uematsu et al, 2015; Zhao et al, 2019). Complementary evidence of disruption in the WNT pathway includes hyperactivation in the presence of DISC‐1 (Brandon et al, 2009), imbalance between canonical and non‐canonical signaling, and altered mRNA levels of WNT‐related genes (Hoseth et al, 2018).…”
Section: Ndd‐associated Multifactorial Disordersmentioning
confidence: 99%
“…GRIA1 is the main excitatory neurotransmitter receptor in the mammalian brain and is activated in a variety of normal neurophysiological processes. These receptors are heteromeric protein complexes with multiple subunits, each subunit has a transmembrane region, and all are arranged to form ligand-gated ion channels [23]. The protein encoded by this gene is an auxiliary subunit of the AMPA ionotropic glutamate receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Physiologically, the drug-induced changes in glutamatergic long-range connections between auditory areas (which presumably draw on both AMPA and NMDA receptors; see discussion in (Schmidt et al, 2012)) could be mediated by short-term changes in synaptic transmission. Specifically, muscarinic agents are known to change AMPA and NMDA receptor function by various mechanisms, including phosphorylation or changes in subunit composition (Marino et al, 1998;Grishin et al, 2005;Shinoe et al, 2005;Di Maio et al, 2011;Lopes et al, 2013;Zhao et al, 2018;Zhao et al, 2019), for review, see (Butcher et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, it is likely that we are observing a net effect of pharmacologically altered muscarinic receptor function on several mechanisms represented in the model, like synaptic connectivity strength and neuronal gain. For example, it is known that muscarinic receptors change glutamatergic synaptic transmission through influencing both NMDA and AMPA receptors (Marino et al, 1998;Grishin et al, 2005;Shinoe et al, 2005;Di Maio et al, 2011;Lopes et al, 2013;Zhao et al, 2018;Zhao et al, 2019); an effect that can be (and was) observed in the estimates of model parameters encoding glutamatergic long-range connections. Similarly, muscarinic receptor activation strongly affects neuronal excitability and gain (McCormick et al, 1993;Shimegi et al, 2016); this effect is captured by estimates of parameters representing the gain of postsynaptic kernels.…”
Section: Limitations and Outlookmentioning
confidence: 99%